Hormonal Contraception and Cervical Cancer Stage: Does Duration of Use Matter? Evidence from Indonesia: Does Duration of Use Matter? Evidence from Indonesia - Meta Zulyati Oktora; Niken Safitri; Nadia Purnama Dewi; Primadella Fegita; Desi Aliefia (CV. AKBAR PUTRA MANDIRI, 2025)
Background: Cervical cancer remains a major public health problem in Indonesia, ranking as the second most common cancer among women. Hormonal contraceptives are widely used, and long-term exposure has been hypothesized to promote cervical carcinogenesis through hormonal modulation of HPV oncogene expression and epithelial proliferation. However, limited evidence is available on their association with the stage of cervical cancer at diagnosis in Indonesian populations. Objective: To examine the association between the duration of hormonal contraceptive use and the clinical stage of cervical cancer among patients at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: A cross-sectional analytic study was conducted involving 80 randomly selected patients from 222 cervical cancer cases in 2019. Data on age, age at marriage, parity, type and duration of contraceptive use, and cervical cancer stage (FIGO classification) were retrieved from medical records. Descriptive statistics were presented as frequencies and percentages, while bivariate associations were analyzed using the Mann–Whitney U test (SPSS v25). Results: The majority of patients were aged 46–55 years (38.6%), married after age 20 (57.1%), multiparous (80%), and predominantly used injectable contraceptives (62.9%). More than half had used hormonal contraceptives for <5 years (55.7%). Cervical cancer was most frequently diagnosed at stage III (47.1%). A statistically significant association was observed between longer duration of hormonal contraceptive use and more advanced cervical cancer stage (p = 0.008). Conclusion: Prolonged hormonal contraceptive use is significantly associated with advanced cervical cancer stage at diagnosis. These findings highlight the need for targeted counseling and routine cervical cancer screening in women using long-term hormonal contraceptives to facilitate earlier detection and improve clinical outcomes.